Brain activity for tactile allodynia: a longitudinal awake rat functional magnetic resonance imaging study tracking emergence of neuropathic pain. Issue 3 (March 2017) - Chang, Pei-Ching; Centeno, Maria Virginia; Procissi, Daniel; Baria, Alex; Apkarian, A. Vania
Abstract : Abstract: Tactile allodynia, a condition in which innocuous mechanical stimuli are perceived as painful, is a common feature of chronic pain. However, how the brain reorganizes in relation to the emergence of tactile allodynia is still largely unknown. This may stem from the fact that experiments in humans are cross-sectional in nature, whereas animal brain imaging studies typically require anaesthesia rendering the brain incapable of consciously sensing or responding to pain. In this longitudinal functional magnetic resonance imaging study in awake rats, we tracked brain activity with the development of tactile allodynia. Before injury, innocuous air-puff stimuli evoked a distributed sensory network of activations, including contralateral somatosensory cortices, thalamus, insula, and cingulate cortex. Moreover, the primary somatosensory cortex displayed a graded response tracking air-puff stimulus intensities. After neuropathic injury, and for stimuli in which the intensity exceeded the paw withdrawal threshold (evoking tactile allodynia), the blood oxygenation level-dependent response in the primary somatosensory cortex was equivalent to that evoked by the identical stimulus before injury. In contrast, nucleus accumbens and prefrontal brain areas displayed abnormal activity to normally innocuous stimuli when such stimuli induced tactile allodynia at 28 days after peripheral nerve injury, which had not been the case at 5 days after injury. Our data indicate that tactile allodynia-related nociceptive inputs are not observable in the primary somatosensory cortex BOLD response. Instead, our data suggest that, in time, tactile allodynia differentially engages neural circuits that regulate the affective and motivational components of pain. Abstract : This work brings insights into the brain circuits involved in development of tactile allodynia, with important implications for how the brain adapts to neuropathic injury.